Factors that influence the implementation and practice of team-teaching for English and Social Science teachers in secondary innovative learning environments in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirement for the degree of Master of Education (Educational Administration and Leadership) at Massey University, Palmerston North, New Zealand - Robinson, Amanda Joy (Massey University, 2019)
Team-teaching in secondary school innovative learning environments (ILEs) in New Zealand is an emergent area of pedagogical practice and there is currently no research exploring the ways it can be supported by school leaders. Team-teaching has emerged as a result of national and global changes in education policy over the past decades. Both ILEs and team-teaching are viewed as providing a pathway to increasing specific knowledge, competencies and dispositions for students in the face of significant global changes. The purpose of this research was to: a) identify important factors that influence the implementation and practice of team-teaching in secondary school ILEs, and; b) seek methods school leaders might employ to optimise factors that influence teachers in their team-teaching practice. Much research has been done about team-teaching at primary level and in inclusive education settings internationally. However existing research largely focuses on the pedagogical practices teachers might use and has not been focused on the leadership of team-teachers in mainstream secondary schools or ILEs. This research aimed to contribute to the literature by examining the specific contextual factors presented by team-teaching in secondary ILEs in New Zealand, and the ways school leaders might optimise these factors. The sample groups for this research were drawn from English and Social Science teachers and heads of department (HoD) from six secondary school ILEs in New Zealand. The research spanned two phases, drawing on a mixed-methods approach to conduct semi-structured interviews with a small sample, before conducting a survey with a larger group of teachers and HoDs. The findings of this research largely reinforce the literature on team-teaching as similar factors were identified. A new contribution is made by considering how time is interconnected with professional relationships, along with the importance of evaluating the impact of changes in practice on students. Collectively, these interconnected factors influence teacher motivation. Additionally, the formation of individual teacher identity is reconceptualised for those team-teaching in highly visible ILEs, when the mitigating effect of career stage is considered. This research also highlights the increased time, space and support that teachers and HoDs require to develop their relational practice to create effective team-teaching partnerships in secondary school ILEs due to their involvement in multiple teams. It is concluded that school leaders may need to re-evaluate the process of supporting teacher change and pedagogical adaptation for those working as team-teachers in secondary ILEs in New Zealand.
The following Figures were removed for copyright reasons but may be accessed via the source provided: Figures 1 (=Robinson et al., 2009, Fig 7); 2 (=Mockler, 2011 Fig 1); 3 (=Guskey, 2002 Fig 1); & 4 (=Merchie et al., 2016 Fig 1).
Keywords: Teaching teams; New Zealand; English language; Social sciences; Study and teaching (Secondary); English teachers; Social science teachers; Attitudes; Classroom environment; 390199 Curriculum and pedagogy not elsewhere classified